2019
DOI: 10.1002/term.2867
|View full text |Cite
|
Sign up to set email alerts
|

Developing a synthetic composite membrane for cleft palate repair

Abstract: An oronasal fistula is a passage between the oral and nasal cavity. Currently, surgical procedures use mucosal flaps or collagen grafts to make a barrier between oral and nasal cavities. Our aim was to develop a cell-free synthetic repair material for closure of nasal fistulas. We surface functionalized electrospun polyurethane (PU) and poly-Llactic acid (PLLA) and composite polymer (PU-PLLA) membranes with acrylic acid through plasma polymerization. Membranes were treated in a layer-by-layer approach to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…La fisura labiopalatina es la malformación congénita craneofacial más frecuente, con una incidencia aproximada de uno por cada 700 recién nacidos vivos (4,40,41). Actualmente, el manejo estándar es el cierre quirúrgico del defecto, tratándose de intervenciones complejas en las que no solo se persigue el cierre del paladar sino la corrección y/o prevención de problemas a menudo asociados de dicción, oclusión dentaria, otitis crónicas y déficits óseos maxilares (4).…”
Section: Fisura Labiopalatinaunclassified
See 1 more Smart Citation
“…La fisura labiopalatina es la malformación congénita craneofacial más frecuente, con una incidencia aproximada de uno por cada 700 recién nacidos vivos (4,40,41). Actualmente, el manejo estándar es el cierre quirúrgico del defecto, tratándose de intervenciones complejas en las que no solo se persigue el cierre del paladar sino la corrección y/o prevención de problemas a menudo asociados de dicción, oclusión dentaria, otitis crónicas y déficits óseos maxilares (4).…”
Section: Fisura Labiopalatinaunclassified
“…La ingeniería tisular se basa en la utilización de biomateriales o scaffolds en los que hacer proliferar las poblaciones celulares. Estos scaffolds deben ser biocompatibles, proporcionando un ambiente ideal para la interacción celular, proliferación, migración celular, diferenciación y al mismo tiempo, tener la capacidad de degradarse una vez lograda su función sin generar productos de desecho que se puedan acumular e interferir en el proceso regenerativo (3,4). Podemos encontrar scaffolds sintéticos, constituidos por polímeros biodegradables (policapronolactona, polietilen-glicol, ácido poliglicólico…), y naturales derivados de matrices extracelulares, hechos a base de proteínas como el colágeno, fibrina, agarosa o la laminina, o a partir de tejidos animales descelularizados.…”
Section: Introductionunclassified
“…Sharif et al developed a plasma-functionalized electrospun composite polymer membrane, modified the fabricated membranes by plasma polymerization, and then implanted them in rats subcutaneously. The results showed that these membranes were biocompatible and angiogenic, providing the possibility for permanent closure of oronasal fistula ( Sharif et al, 2019 ). Lee et al created cell sheets derived from hMSCs and SHEDs for bone repair of cleft palate and found that the cell sheets led to calcification in vitro , which indicated that osteogenic stem cell sheets may become a new choice for the reconstruction of cleft palate ( Lee J.-M. et al, 2019 ).…”
Section: Dental Implant Tissue Engineeringmentioning
confidence: 99%
“…There are numerous techniques to prevent and treat postoperative palatal fistula using local or distant tissues 5,[7][8][9][10][11][12] . Attempts have also been made to develop synthetic biomaterials that can decrease the incidence of postoperative fistula 13 . There are several recent reports of favorable outcomes after the use of acellular dermal matrix (ADM) 4,5,14,15 .…”
mentioning
confidence: 99%